Effect of visual endotracheal tube combined with bronchial occluder on pulmonary ventilation and arterial blood gas in patients undergoing thoracic surgery - Xin, Jing; Fan, Xiu-juan (Frontiers in Surgery, 2023)
Background: To investigate the effect of visual endotracheal tube combined with bronchial occluder on pulmonary ventilation and arterial blood gas in patients undergoing thoracic surgery. Methods: Ninety patients who underwent thoracic surgery under anesthesia and required pulmonary ventilation at our hospital from May 2020 to December 2021 were collected. The patients were divided into three groups according to different intubation methods: visual double-lumen endotracheal tube group (VDLT group), bronchial occluder group (BO group), and VDLT+BO group. Clinical data and laboratory test data were collected from the three groups. Additionally, the three groups were compared in terms of peak airway pressure, time to correct positioning, pulmonary ventilation time, hemodynamics before and after intubation, intubation success rate, and postoperative recovery. Results: The VDLT+BO group was superior to the BO group or VDLT group in airway peak pressure, time to correct positioning, pulmonary ventilation time, intubation success rate, and hemodynamics after intubation (P < 0.05). In the comparison of postoperative recovery, the postoperative pain score, white blood cell level, incidence rate of pneumonia, hospital stay and hospitalization costs in the VDLT + BO group were significantly lower than those in the BO group or VDLT group (P < 0.05). Conclusion: The visual endotracheal tube combined with bronchial occluder is effective in pulmonary ventilation during thoracic surgery under anesthesia, and can improve arterial blood gas in patients.